(untitled) (Journal of Parents and Teachers, 2020)
Two teachers explain the experience they have had after doing their End-of-Graduate Work (TFG) during confinement and share their opinion about STEM education as a perspective of the new educational paradigm. They define what it is, propose scales for its assessment and stress the importance of its promotion in non-formal educational settings.